STINK BUGS COLLECTED ON CANOPY OF DIFFERENTS TREE SPECIES AIMING. PENTATOMIDAE-1 - Costa, Ervandil Corrêa (1999)
Insects were collected on ten tree species aiming indentify the ones that belonged to the Pentatomidae family and their respectives host plants. The survery was conducted in São Sepá, RS, during December of 1992 and entire 1993. To collect the insects a conical funnel with a bag was used. One sample was taken from shaking tree branches ten times over the funnel. Isect sampling were carried out at 15 days intervals. Pentatomidae were observed on seven tree species and ten Pentatomidae species were collected. The tree camboim (Myrciaria tenella) was the preferential host and Thyanta (Argosoma) patruelis was the species that presented the host diversity.